Efektivitas Pembelajaran STEM Pada IOT Smart Proyek Hemat Energi Untuk Meningkatkan Hasil Belajar Siswa Kelas - Supriati, Supriati; Karyadinata, Rahayu; Muhammad Minan Chusni, Muhammad Minan Chusni (Alpatih Harapan Semesta, 2025)
This study aims to analyze the effectiveness of implementing STEM (Science, Technology, Engineering, and Mathematics) learning through an energy-saving Internet of Things (IoT) project in improving students’ learning outcomes in Grade IX at MTsN 7 Cirebon. The research employed a pre-experimental design with a one group pretest–posttest design, involving 30 students as research participants. A multiple-choice test instrument was used to measure students’ conceptual understanding before and after the learning intervention. Data were analyzed descriptively and through N-gain analysis to determine the learning effectiveness. The results showed that the students’ average pretest score of 64.00 increased to 72.07 after the intervention. The mean N-gain score reached 20.24%, with a standard deviation of 17.21 and a score range from -25.00 to 46.43. According to Hake’s gain criteria, this result falls into the low category, and based on the learning effectiveness criteria, it is categorized as “ineffective.” A total of 40% of students were in the medium category, 46.7% in the low category, and 13.3% experienced decreased learning outcomes. Although the overall effectiveness is classified as low, the findings indicate that project-based STEM learning with IoT has the potential to enhance students’ conceptual understanding and learning motivation. Further improvements in instructional strategies, more intensive guidance, and technology integration adapted to students’ needs are recommended to achieve more optimal learning outcomes.